NAVIGATING IMPOLITENESS IN POLITICAL DISCOURSE ON SOCIAL MEDIA: A CYBER PRAGMATICS ANALYSIS OF THE 2024 INDONESIAN PRESIDENTIAL ELECTION - Setiawati, Eti; Salamah, Salamah (ppjbsip, 2025)
This study explores the phenomenon of impoliteness in political discourse on social media during the 2024 Indonesian presidential election. Utilizing a descriptive qualitative approach and document study, tweets discussing the three presidential candidate pairs were analyzed using Brown-Levinson and Asim Gunawan's cyber pragmatics theories. The data consists of tweets from social media X/Twitter, revealing frequent violations of both positive and negative face, with many instances of hate speech and personal attacks, particularly among netizens labeled as buzzers. The results show that regardless of the supported presidential and vice-presidential candidate pairs, impolite utterances are prevalent in social media discussions. The principle of maintaining a positive face, which is the desire to be respected, and a negative face, which is the desire to act freely, are widely violated by Indonesian netizens. Instead of engaging in polite discourse to contest ideas, there are numerous instances of personal attacks, including the spread of personal data and allusions to SARA issues. The principles of kurmat, andhap asor, empan papan, and tepa selira, as part of Eastern culture, are also widely violated, leading to separatist movements and increased political polarization among the public. The study highlights the erosion of Eastern cultural politeness principles, contributing to increased political polarization. Sensitivity and irritation also occur more easily, creating opportunities for various types of hate speech. The insights gained offer a deeper understanding of the motivations behind online impoliteness and the potential for preventive measures to maintain social cohesion during democratic processes.